2017
DOI: 10.1021/acs.oprd.6b00412
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Dimroth Rearrangement Route to AZD8931

Abstract: Recently, the aminoquinazoline motif has been highly prevalent in anticancer pharmaceutical compounds. Synthetic methods are required to make this structure on a multikilo scale and in high purity. The initial route to aminoquinazoline AZD8931 suffered from the formation of late-stage impurities. To avoid these impurities, a new high-yielding Dimroth rearrangement approach to the aminoquinazoline core of AZD8931 was developed. Assessment of route options on a gram scale demonstrated that the Dimroth rearrangem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Compared to gefitinib or erbB2 inhibitors, AZD8931 was a much more potent inhibitor of EGF-driven cellular proliferation in multiple tumour cell lines 46 William et al reported an industrial scale synthesis using Dimroth rearrangement route as has been shown to be utilized to some of commercially available drug of this series. 47 All in all, Dimroth Rearrangement is the most versatile method to synthesize amino quinazoline derivatives. A general synthetic approach for isolation of such compounds is depicted in Scheme 18.…”
Section: Scheme 16 Initial Synthesis Of Vandetib (V)mentioning
confidence: 99%
“…Compared to gefitinib or erbB2 inhibitors, AZD8931 was a much more potent inhibitor of EGF-driven cellular proliferation in multiple tumour cell lines 46 William et al reported an industrial scale synthesis using Dimroth rearrangement route as has been shown to be utilized to some of commercially available drug of this series. 47 All in all, Dimroth Rearrangement is the most versatile method to synthesize amino quinazoline derivatives. A general synthetic approach for isolation of such compounds is depicted in Scheme 18.…”
Section: Scheme 16 Initial Synthesis Of Vandetib (V)mentioning
confidence: 99%
“…This reaction typically proceeds by conversion of an alcohol to a carbonyl functionality via transition-metal-catalyzed oxidative dehydrogenation followed by condensation with an amine to form an imine intermediate and subsequent reduction of the imine with metal-hydride to form an N -alkylated product. Since the pioneering work by Watanabe et al and Grigg et al, several reports have been published for N -alkylation of amines with primary alcohols using Co, Fe, Ir, Mn, Ni, and Ru catalysts. Most of these reaction conditions are characterized by the use of specialized ligands ( N -heterocyclic carbene, pincer, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some unexpected nitro impurities are easily generated in the nitration reaction, such as nitro regioisomers 18 and 19 and dinitro 20 , as shown in Figure . For the nitroreduction, the exothermic system and side reactions require strict control so as to prevent potential safety hazards, in which intermediates (nitroso 21 , hydroxylamine 22 ), in particular, hydroxylamine 22 , are prone to have side reactions and generate impurities such as amide 23 , azoxy 24 , azo 25 , and hydrazo 26 , , as shown in Figure . In addition, route III requires high-quality equipment so as to tolerate the high reaction temperature (130 °C).…”
Section: Introductionmentioning
confidence: 99%